2019
DOI: 10.1016/j.ejpb.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation method on the surface properties and UV imaging of indomethacin solid dispersions

Abstract: Submission: European Journal of Pharmaceutics and Biopharmaceuticsthe dissolution of indomethacin. This work thus highlights the importance of having both complimentary IDR and whole dosage imaging techniques in giving a better understanding of solid dispersion systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…UV imaging has also been useful in other applications, such as biorelevant characterisation of salts, solid dispersions, transdermal patches, and hydrogels (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Alongside, the potential of the technique in relation to quality control assessment has been suggested (20,34,37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV imaging has also been useful in other applications, such as biorelevant characterisation of salts, solid dispersions, transdermal patches, and hydrogels (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Alongside, the potential of the technique in relation to quality control assessment has been suggested (20,34,37).…”
Section: Introductionmentioning
confidence: 99%
“…This combination was used to analyse drug content of drug-excipient compacts prior to IDR determination with an Actipix SDI 300 (39). Focus variation microscopy has also been employed to suggest that rough drug compact surfaces, may increase the variation of IDR measurements (14,34,35).…”
Section: Introductionmentioning
confidence: 99%
“…Asare-Addo et al 2019 also investigated a spray drying, freeze-drying and homogenizing-freeze drying technique on indomethacin soluplus amorphous solid dispersions. The authors also found the different manufacturing techniques to impact on the surface properties of compacts for intrinsic dissolution rate (IDR) measurements [46]. The impact of the freeze-drying processes on the dissolution rate of solid dispersions containing D-glucosamine HCl (GLU and PXM ((4-hydroxy-2-methyl-N-(2piridyl) 2H-1,2-benzothiazine-3-carboxamide-1, 1-dioxide) and its impact of the charging properties were assessed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Biopharmaceutics classification system (BCS) Class II drugs are characterized by low solubility and high membrane permeability, so that the dissolution of drugs from dosage formulation is the ultimate rate-limiting step [1], resulting in high permeability but low bioavailability. Many strategies have been applied to improve the dissolution rate and bioavailability of active pharmaceutical ingredients (APIs) including formulation changes, industry strategies, method optimum, etc.…”
Section: Introductionmentioning
confidence: 99%